Humic acid from leonardite for cadmium adsorption and potential applications - MENG Fande; YUAN Guodong; WEI Jing; BI Dongxue; WANG Hailong; LIU Xingyuan (浙江大学学报. 农业与生命科学版)
Cadmium (Cd) is a toxic and carcinogenic contaminant released from a wide range of industries. Its accumulation in soil and water is of growing environmental and health concerns. Thus, there is an increasing demand for materials that are effective for Cd adsorption, economically feasible, and unlikely to create new environmental problems.Humic acid (HA) is ubiquitous in soil and sediment. It can also be extracted from lignite and leonardite, which can be viewed as ancient biochar and oxidized ancient biochar, respectively. Being abundant in carboxyl and hydroxyl groups (—COOH, —OH), HA has a strong propensity for adsorbing heavy metal cations by forming inner-sphere complexes, thus reducing their mobility and bioavailability. A leonardite (Leo) from Xinjiang, China was used to produce HA by ultrasonically dispersing Leo in 0.1 mol/L NaOH solution at 40℃ for 30 min, and then flocculating the supernatant with 6 mol/L HCl. The obtained HA (Leo-HA) was characterized for its surface properties by scanning electron microscopy (SEM) and Fourier transform infrared spectroscopy (FTIR), and was analyzed for elemental compositions, carboxyl group, and isoelectric point (pI). Further, its adsorption characteristics were determined by kinetic and batch experiments, and its potential applications in removing Cd2+ from water and immobilizing Cd2+ in soils were assessed based on its technical reliability, economic feasibility, and environmental impact. For environmental relevance, a relatively low range of Cd2+ concentrations (0-100 mg/L) was used in adsorption experiment, during which the pH of solution was maintained constant.Results showed that Leo-HA had a low pI of 2.7 and a high C content of 58.68%, which is not unusual for coal-derived HA. FTIR confirmed the abundance of —COOH and —OH groups. The carboxyl group was determined at 5.81 mol/kg. The low Cd concentration (0.15 mg/kg) of Leo-HA met the prerequisite for safe use in agricultural land, as regulated by Farmland Environmental Quality Standards. Kinetic studies showed that Cd2+ adsorption onto Leo-HA reached equilibrium in 8 h and the process was pH-dependent. The adsorption increased with pH within 2.0-6.0, and then decreased as pH further increased to 7.0．This is because Leo-HA starts to dissolve as solution pH approaches to neutral. Adsorption data were better fitted into Langmuir equation (R2=0.991) than Freundlich equation (R2=0.891), suggesting the monolayer nature of Cd2+ adsorption onto Leo-HA. At pH 5.0, the maximum adsorption capacity (Qm) derived from the Langmuir equation was 137.37 mg/g, which was equivalent to 71% of the carboxyl groups of Leo-HA. This Qm was much higher than what had been reported in the literature for lignite, lignite-derived HA, and soil HA. A simple comparison at pH 4.3 and an initial Cd2+ concentration of 80 mg/L showed that the Leo-HA adsorbed more Cd2+ (86.97 mg/g) than the reference HA 1R106H (73.49 mg/g) from IHSS did, even though the later had a higher carboxyl content (6.82 mol/kg). This apparent discrepancy was due to the fact that dissolution of 1R106H was observed at pH 4.3, whereas the Leo-HA was stable at this pH.Leonardite is abundant across China. Leo-HA has the advantages of low cost, high adsorption capacity, and low Cd content, thus it is a prospective adsorbent for immobilizing Cd2+ in contaminated soils or removing Cd2+ from water. Lime has widely been used to immobilize Cd2+ in soils, but it tends to reduce soil organic matter content, damage soil structure, and pose a hazard to the safety of its users in the field. In contrast, Leo-HA is beneficial to soil structure and soil quality, as well as safe to handle in the field. Field trials of applying Leo-HA onto heavy metal contaminated soils would be a logical step to follow.